2007
DOI: 10.2503/jjshs.76.345
|View full text |Cite
|
Sign up to set email alerts
|

Starch Degradation of Detached Apple Fruit in Relation to Ripening and Ethylene

Abstract: The physiology of starch degradation in relation to ripening and ethylene was investigated using 'Tsugaru' (earlymaturing) and 'Fuji' (late-maturing) apples (Malus domestica Borkh.). Fruits were harvested at immature and mature stages, and treated with ethylene and 1-methylcyclopropene (1-MCP). In immature fruit of both cultivars, starch content rapidly decreased during storage at 25°C, and 1-MCP had little effect on this change. Ethylene treatment slightly stimulated the degradation of starch, but differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…Although fruit appeared physiologically more mature based on their potential to produce ethylene, the 2004 fruit were commercially less mature in terms of their quality parameters. This apparent contradiction is of interest and in accordance with the results reported by Thammawong and Arakawa,2 who reported that immature apples could not respond to endogenous and exogenous ethylene in order to induce their climacteric. They also reported that starch degradation was not related to the climacteric behaviour of the fruit or to ethylene production.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Although fruit appeared physiologically more mature based on their potential to produce ethylene, the 2004 fruit were commercially less mature in terms of their quality parameters. This apparent contradiction is of interest and in accordance with the results reported by Thammawong and Arakawa,2 who reported that immature apples could not respond to endogenous and exogenous ethylene in order to induce their climacteric. They also reported that starch degradation was not related to the climacteric behaviour of the fruit or to ethylene production.…”
Section: Resultssupporting
confidence: 88%
“…This method to determine optimum harvest date is not able to follow changes in the maturity of apples in orchards. Internal ethylene concentrations are, for example, poorly related to starch degradation2 and changes in firmness and SSC in orchards 3. For all these reasons, other indicators are needed and we therefore propose a study to determine the activities of antioxidant enzymes 4…”
Section: Introductionmentioning
confidence: 99%
“…As fruit ripen, starch is degraded and sugar content increases, providing the sweetness associated with changing fruit taste (Blanco and others 1992). Thammawong and Arakawa (2007) studied the degradation of starch in two apple cultivars and noticed that starch degradation after harvest seems highly related to climacteric and physiological changes in fruit, such as increased ethylene production and respiration rate. Even more starch degradation related is glucose, the content of which generally rises in both cultivars during the shelf life of fruit (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This result was then validated by water‐stressed and shading experiments, in which carbon storage during fruit growth was (respectively) increased and decreased. Although the link between starch degradation and respiration climacteric in fruits has already been proposed in, for example, banana (Seymour, ), kiwifruit (Han & Kawabata, ) and apple (Thammawong & Arakawa, ), it is interesting to note that cell wall degradation substantially contributes to the energy peak. Cell wall remodelling at ripening is well documented.…”
Section: Discussionmentioning
confidence: 99%